Understanding the Role of Active Lattice Oxygen in CO Oxidation Catalyzed by Copper-Doped Mn2O3@MnO2 - Hao Zhang; Tan Meng; Min Zhang; Pengyi Zhang; Peizhe Sun; Huinan Li; Yangyang Yu (Molecules)
Although the hopcalite catalyst, primarily composed of manganese oxide and copper oxide, has been extensively studied for carbon monoxide (CO) elimination, there remains significant potential to optimize its structure and activity. Herein, Cu-doped Mn3O2@MnO2 catalysts featuring highly exposed interfacial regions were prepared. The correlation between interfacial exposure and catalytic activity indicates that the interfacial region serves as the active site for CO catalytic oxidation. The characteristic adsorption of CO by Cu species significantly enhances the catalytic activity of the catalyst. And XPS and ICP-OES analyses reveal that Cu ions coexist in both the interlayer and lattice of δ-MnO2. Furthermore, XPS analysis was employed to quantify the average oxidation state (AOS) of Mn and the molar ratios of oxygen species, demonstrating that both surface-adsorbed oxygen and surface lattice oxygen act as reactive oxygen species in the catalytic reaction, playing a crucial role in CO oxidation. Notably, the surface reactive oxygen species influence the adsorption of CO onto Cu species, and the replenishment of these reactive species is identified as the rate-limiting step in the CO catalytic oxidation process.